Use of a Fungicide to Reduce Stomatal Conductance for Production of Sweet Corn Planted at Different Populations with Limited Irrigation - D. W. Sweeney; M. B. Kirkham (Kansas Agricultural Experiment Station Research Reports, 2019)
Sweet corn in 2018 was affected by irrigation, plant population, and a fungicide applied for stomatal control. Even though measured stomatal conductance was unaffected and no disease pressure was noted, applying fungicide at V6 more than doubled the number of harvested ears per acre and per plant, but an additional application at R1 did not increase harvested ears. Applying 1 inch of irrigation at the VT growth stage resulted in approximately 20% greater number of harvested ears per acre and ears per plant, but did not increase fresh weight. Under these dry conditions, increasing plant population tended to decrease harvested ears per acre and ears per plant, especially when no fungicide was applied or with no irrigation.
Keywords: fungicide; stomatal control; sweet corn; population; irrigation